THE CORRELATION BETWEEN LISTENING STRATEGIES USED BY 4TH SEMESTER STUDENTS OF UNRIKA AND THEIR LISTENING COMPREHENSION - Putri, Aulia; Surlitasari Dewi, Desi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
This study aimed to find out the most dominant listening strategies used by the students and to determine the correlation between the use of listening strategies and their listening comprehension. The type of the research was quantitative with correlational design. This study used a population of the 4th semester students of English Education Study Program, University of Riau Kepulauan, in which the sample was selected by total sampling technique. Data were collected by using listening strategy questionnaire and listening test. To analyze the data, descriptive statistics (Mean and Standard Deviation) were used to find out the most dominant strategies to the ones that were rarely used by students in completing listening comprehension task. Second, to find out whether or not Â there was a significant correlation between listening strategies used and listening skills, the data were analyzed by Â using Pearson Correlation to determine the correlation between two variables, listening strategies and listening comprehension.